Newer Azitidinoyl Thiazolidinoyl And Formazan-1, 3 Thiazolyl Pyridines And Their Biological Activities - Bhati, Sudhir Kumar (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACTA series of 2-(2ï‚¢-substitutedarylidenylimino-1ï‚¢,3ï‚¢-thiazol-4ï‚¢-yl)aminopyridines (3a-3d), 2-[2ï‚¢-(3ï‚¢ï‚¢-chloro-2ï‚¢ï‚¢-oxo-4ï‚¢ï‚¢-substitutedaryl-1ï‚¢ï‚¢-azetidinyl)-1ï‚¢,3ï‚¢-thiazol-4ï‚¢-yl] amino pyridines (4a-4d), 2-[2ï‚¢-(2ï‚¢ï‚¢-substitutedaryl-4ï‚¢ï‚¢-thiazolidinon-3ï‚¢ï‚¢-yl)-1ï‚¢,3ï‚¢-thiazol-4ï‚¢-yl] aminopyridines (5a-5d) and 2-[2ï‚¢-(1ï‚¢ï‚¢-phenyl-3ï‚¢ï‚¢-substituted aryl-formazan-4ï‚¢ï‚¢-yl)-1ï‚¢,3ï‚¢-thiazol-4ï‚¢-yl]aminopyrid-ines (6a-6d) were prepared in present study. The structure of all these newly synthesized compounds was confirmed on the basis of spectral (IR, 1HNMR and mass) and analytical data. Out of four azetidinone derivatives, 2-[2ï‚¢-(3ï‚¢ï‚¢-chloro-2ï‚¢ï‚¢-oxo-4ï‚¢ï‚¢-o-hydroxyphenyl-1ï‚¢ï‚¢-azetidinyl)-1ï‚¢,3ï‚¢-thiazol-4ï‚¢-yl]aminopyridine (4c) was found to be the most potent compound of this series. This compound exhibited maximal insecticidal activity in comparison to standard, parathion at three tested concentrations. Furthermore, this compound also possessed comparable antifungal activity with fluconazo.